Pembelajaran Tari Sebagai Penguatan Kecerdasan Emosional Anak Usia Dini : Studi Kasus pada Paud Lab School Universitas Negeri Semarang - Siti Nurjanah; Lesa Paranti (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the importance of strengthening emotional intelligence in early childhood as a foundation for character building and social abilities. One approach used is through dance education. The purpose of this study is to examine the dance learning process at the Lab School Early Childhood Education (PAUD) of Universitas Negeri Semarang and to analyze the function of dance education in strengthening emotional intelligence. The method used is descriptive qualitative with observation, interview, and documentation techniques. The results show that dance education at the UNNES Lab School PAUD is part of the intraclass curriculum. The dance material provided is adjusted to the learning themes and objectives. The dance learning process is conducted in an enjoyable manner, helping to strengthen children's emotional intelligence. This is evident in their ability to control themselves and in their social skills, including learning to wait their turn, follow rules, manage emotions, cooperate, and show empathy during the dance process. Through age-appropriate approaches and teacher support, dance learning serves as an effective medium for fostering aspects of emotional intelligence in early childhood.